Current Technical State of the Ground Pumping Station - Mirzaev Mirzabek; Toirov Mukhriddin (Zien Journals, 2023)
This article provides information on the post-reconstruction indicators and current technical condition of Kuyimozor pumping station located in the Amudarya basin.
Keywords: Pump; unit; pumping station; reconstruction